Eventos interconductuales relacionados con la presencia del insomnio en personas que asisten a la Comunidad de Laicos Eucarísticos Marianos (CLEM). Un estudio de caso. (2019)
This research presents the results of a molar analysis of interbehavioral events associated with the presence of insomnia in people attending the Marian Eucharistic Lay Community (CLEM) from the Interbehaviorismf theory. The objective is to identify the interbehavioral events related to the presence of insomnia in the population under study, identifying the means of contact, the interbehavioral history and determining the situational factors that are presents, intervene and facilitate the insomnia disorder